A polydimethylsiloxane modified nano titanium dioxide super-hydrophobic coating, coating and preparation method thereof
By adopting the polymailing siliconane -alkane -modified nano -titanium titanium dioxide ultra -hydrophobic coating, the adhesion and insufficient durability of nano -titanium dioxide coating on the glass substrate are solved, and the good adhesion, durability and self -self -durability of the coating are realized. Clean effect.
Patent Information
- Application Number
- CN202311095458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-08-28
AI Technical Summary
The adhesion and durability of the existing nanotitanium dioxide self-cleaning coating on glass substrates is insufficient, and nanoparticles are prone to agglomeration and affect the coating function.
Polymailing siliconxane modified nano-titanium titanium hydrophobic coatings can be used. By decentralized nano-titanium dioxide particles in the solve, add polyxide siliconide and curing agent to form organic-inorganic composite coating to improve the coating coating Attachment and decentralization.
The good adhesion and durability of the coating on the glass substrate are realized, the hydrophobicity and photocatalytic activity of the coating can be improved, and the organic pollutants can be effectively degraded under ultraviolet light to maintain the self -cleaning effect.
Smart Images

Figure HDA0004419111740000011 
Figure HDA0004419111740000012 
Figure HDA0004419111740000021
Abstract
Description
Technical Field
[0001] The invention relates to a novel self-cleaning glass coating, in particular to a polydimethylsiloxane-modified nano titanium dioxide super-hydrophobic coating, a coating and a preparation method thereof. Background Art
[0002] With the development of nanotechnology, a new type of self-cleaning coating of nano-titanium dioxide (TiO2) has attracted wide attention, especially in the construction and automotive industries. Studies have shown that titanium dioxide has excellent photocatalytic activity. When titanium dioxide is exposed to ultraviolet rays (such as sunlight), a photocatalytic reaction will occur to generate oxidative free radicals and superoxide ions; these free radicals and ions will further react with water and oxygen to generate strong oxidizing hydroxyl and hydrogen peroxide; hydroxyl and hydrogen peroxide can decompose organic and inorganic substances attached to their surface, such as dirt and bacteria, to achieve the purpose of photodegradation. This characteristic is called "self-cleaning". However, as a powdered inorganic material, nano-titanium dioxide is difficult to adhere firmly to the glass substrate. Therefore, it is necessary to add organic materials to the coating to form an organic-inorganic composite material, which can improve the adhesion and durability of the titanium dioxide coating. Organic matter can also provide solubility, making the coating easier to prepare and apply.
[0003] Polydimethylsiloxane (PDMS) is a common organosilicon compound, often used as a binder material. At the same time, due to its high softness, temperature resistance, super hydrophobicity and other properties, it is widely used in surface modification and coating materials. One of the common modifications is to use PDMS for the preparation of hydrophobic coatings. The coating surface prepared by the modified material is hydrophobic, and the contact angle of water droplets on the surface will increase, and the water droplets will roll or slide more easily, thereby achieving wettability control and liquid anti-attachment. When rain or clean water washes the glass, due to the super hydrophobicity of the coating, the water will form small beads and carry away the decomposed dirt, thereby achieving self-cleaning. This hydrophobic coating has a wide range of applications and potential in the fields of self-cleaning surfaces, anti-pollution coatings, and liquid motion control.
[0004] Patent document CN101962514A reports a long-durability lotus leaf-shaped self-cleaning coating material suitable for large-area preparation and its preparation method. The disadvantage of this method is that the nanoparticles are prone to agglomeration, which affects the performance of the coating. Patent document CN113683953A reports a preparation method of a super-hydrophobic photocatalytic self-cleaning coating with renewable dual self-cleaning function. This method cannot achieve good adhesion between the coating and the substrate surface. Summary of the invention
[0005] In order to solve the above problems of the prior art and improve the hydrophobicity of titanium dioxide and the dispersibility in the coating, the present invention provides a polydimethylsiloxane-modified nano titanium dioxide super-hydrophobic coating, coating and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] The invention provides a polydimethylsiloxane-modified nano titanium dioxide super-hydrophobic coating, which comprises polydimethylsiloxane-modified nano titanium dioxide particles, polydimethylsiloxane, a solvent and a curing agent; the mass ratio of the polydimethylsiloxane-modified nano titanium dioxide particles to the polydimethylsiloxane is (20-100) mg:(5-30) g.
[0008] The present invention provides a method for preparing a polydimethylsiloxane-modified nano-titanium dioxide super-hydrophobic coating, comprising:
[0009] (1) adding polydimethylsiloxane modified nano titanium dioxide particles into a solvent and ultrasonically dispersing them for 30 to 120 minutes;
[0010] (2) adding PDMS and a curing agent, stirring for 30 to 60 minutes, and finally standing for 1 to 3 hours until the bubbles disappear, thereby obtaining the coating.
[0011] As a preferred embodiment, the method for preparing the polydimethylsiloxane-modified nano titanium dioxide particles comprises:
[0012] (1) Ultrasonic dispersion of TiO2 particles with a particle size of 15 to 200 nm in a tetrahydrofuran (THF) solution at room temperature for 30 to 60 minutes to form a suspension A;
[0013] (2) adding PDMS to suspension A at room temperature and stirring until THF is completely volatilized to form latex B; the mass ratio of TiO2 particles to PDMS is (0.05-2) g:(5-20) g;
[0014] (3) Then, add the toluene solution to the latex B, stir evenly and centrifuge for 5 to 15 minutes. This step can be repeated 3 to 10 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0015] (4) The wet precipitate C is dried at 60-120° C. for 12-24 h to obtain polydimethylsiloxane-modified nano-titanium dioxide particles, which are denoted as M-TiO2.
[0016] The invention provides a polydimethylsiloxane modified nano titanium dioxide super-hydrophobic glass coating, which is obtained by coating the coating on a glass substrate.
[0017] The coating is an organic-inorganic composite coating, with Si, Ti, C, and O elements evenly distributed, and TiO2 is anatase type with positive tetravalence. The presence of TiO2 makes the coating photocatalytically active; the addition of PDMS makes the coating elastic and tearable without breaking, and the coating surface is even and free of cracks. Since the PDMS material itself is hydrophobic, using it to modify TiO2 to make a film can make the coating super-hydrophobic, with a water contact angle of nearly 160°, similar to the surface of a lotus leaf that is not stained by mud, and water droplets carry away surface pollutants when rolling down.
[0018] The invention provides a method for preparing a polydimethylsiloxane modified nano titanium dioxide super-hydrophobic glass coating, which is obtained by coating the coating on a glass substrate by an immersion and pulling method. The coating is evenly distributed on the glass substrate and has strong adhesion.
[0019] The specific preparation method of polydimethylsiloxane modified nano titanium dioxide super hydrophobic glass coating is as follows:
[0020] (1) Pretreatment of glass substrate:
[0021] 1) Immerse the glass substrate in a strong acid or alkaline solution for cleaning, such as a HCl-H2O2 mixture or a H2SO4-H2O2 mixture, to remove inorganic salts and metal ions on the surface;
[0022] 2) Take out the glass substrate, place it in deionized water and ethanol solution for ultrasonic treatment for 30 to 60 minutes respectively to remove the acid and alkali cleaning solution and residual impurities on its surface, and finally place it in an oven to dry for use.
[0023] It should be noted that the specific cleaning steps and the choice of cleaning agent will vary according to the requirements of the experiment and the characteristics of the glass substrate. During the operation, appropriate personal protection measures should be used, such as wearing gloves and goggles, and avoiding direct contact with cleaning solutions and acidic solutions.
[0024] (2) Preparation steps of coating:
[0025] 1) placing the pretreated glass substrate vertically above the coating, and using a puller to immerse and pull the coating at a rate of 60 to 180 mm / s to obtain a wet coating;
[0026] 2) The coated glass substrate is placed at room temperature for 12 to 24 hours for curing to obtain a dry self-cleaning glass coating.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The coating of the present invention comprises polydimethylsiloxane-modified nano titanium dioxide and polydimethylsiloxane, and the presence of TiO2 makes the coating formed by the coating have good photocatalytic activity, can degrade organic pollutants under ultraviolet irradiation, and makes the coating have self-cleaning property. Polydimethylsiloxane is used as hydrophobic modifier and binder at the same time, and first nano titanium dioxide can improve the hydrophobicity of coating after polydimethylsiloxane modification, and excellent super-hydrophobicity enables it to resist the attachment of dirt, dust and water stains, reduces the frequency of cleaning and maintenance, and improves the finish and transparency of glass surface; and after polydimethylsiloxane modification, its dispersibility and compatibility in organic solvent (such as: n-hexane, PDMS) can be well controlled, and TiO2 is effectively improved. The uniformity of distribution in coating is conducive to coating quality and stability. Secondly, polydimethylsiloxane binder and polydimethylsiloxane-modified nano titanium dioxide are used to form coating, so that coating hydrophobicity is further improved, and has higher high temperature resistance, can keep its self-cleaning performance under high temperature environment, and is suitable for application under various high temperature conditions.
[0029] The preparation method of the polydimethylsiloxane modified nano titanium dioxide particles of the present invention is simple, low in cost, short in preparation cycle and does not require high-temperature calcination, and has broad application prospects.
[0030] The coating of the present invention has uniform thickness, and the materials used in the coating are environmentally friendly, do not contain toxic and harmful substances, and do not pollute the environment. The coating has high durability, can maintain its self-cleaning effect for a long time during use, does not require frequent cleaning or maintenance, can resist the erosion of ultraviolet rays, acid and alkali environments, and prolongs the service life of the coating. It can be used on architectural glass, automotive glass, solar panels, optical equipment, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a cross-sectional morphology diagram of the photocatalytic self-cleaning coating obtained in Example 1 (scanning electron microscope photograph).
[0032] Figure 2 This is a surface morphology image of the photocatalytic self-cleaning coating obtained according to Example 1 (scanning electron microscope image).
[0033] Figure 3 This is the elemental composition diagram of the photocatalytic self-cleaning coating obtained according to Example 1.
[0034] Figure 4 This is the water droplet distribution diagram of the photocatalytic self-cleaning coating obtained according to Example 1.
[0035] Figure 5 This is a water contact angle diagram of a glass plate not coated with a photocatalytic self-cleaning coating obtained according to Example 1.
[0036] Figure 6This is a water contact angle diagram of a glass plate after being coated with a photocatalytic self-cleaning coating obtained in Example 1.
[0037] Figure 7 The water contact angle diagrams of different photocatalytic self-cleaning coating surfaces obtained according to Examples 1 to 5 are shown.
[0038] Figure 8 It is a graph showing the degradation of methylene blue of different photocatalytic self-cleaning coatings obtained in Examples 1 to 5 under ultraviolet light irradiation.
[0039] Fig. 9 This is a physical picture of the photocatalytic self-cleaning coating obtained according to Example 1.
[0040] Fig.10 It is a comparison chart of the static precipitation after ultrasonic dispersion of M-TiO2 obtained by PDMS modification in Example 1 and unmodified TiO2 in Comparative Example 2 in n-hexane solvent.
[0041] Fig.11 These are transmission electron micrographs of the M-TiO2 modified by PDMS in Example 1 and the unmodified TiO2 in Comparative Example 2.
[0042] Fig.12 Graphs of surface water contact angles of uncoated glass sheets and self-cleaning coated glass sheets obtained in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION
[0043] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0044] Embodiment 1:
[0045] According to the preparation method proposed in the present invention, a polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating is prepared:
[0046] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0047] (2) Add 9.05 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0048] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0049] (4) drying C in an oven at 100°C for 24 h to obtain hydrophobically modified TiO2 particles, i.e., M-TiO2;
[0050] (5) Add 0.5 g of M-TiO2 to 6 mL of n-hexane and disperse by ultrasonic for 30 min;
[0051] (6) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D;
[0052] (7) immersing the glass substrate in a HCl-H2O2 mixture for cleaning to remove inorganic salts and metal ions on the surface;
[0053] (8) The glass substrate is taken out and ultrasonically treated in deionized water and ethanol solution for 30 min respectively to remove the acid and alkali cleaning solution and residual impurities on the surface, and finally placed in an oven to dry for later use;
[0054] (9) placing the pretreated glass substrate vertically above the coating slurry D, and using a puller to immerse and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0055] (10) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0056] The cross-sectional and surface morphology of the polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating prepared in Example 1 were characterized. Figure 1 and Figure 2 As shown. It can be seen that the thickness of the obtained coating is about 140μm and it is evenly coated on the glass plate; in addition, the element composition of the coating is as follows Figure 3 As shown, it can be seen that the four elements Si, Ti, C, and O are evenly distributed on the coating surface.
[0057] The hydrophilic and hydrophobic properties of the polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating prepared in Example 1 were tested. First, water drops were dropped on the photocatalytic self-cleaning glass coating to observe the distribution of water drops. For the convenience of observation, the water drops were dyed. The results are as follows: Figure 4 As shown, it can be seen that the water on the coating is in the form of water droplets and is not spread out into a water film, indicating that the coating has good hydrophobicity. In order to accurately measure the contact angle between the water droplet and the glass plate, the surface water contact angle of the coating is measured. The results are shown in Figure 5 and Figure 6As shown, the water contact angle of the glass plate without photocatalytic self-cleaning coating is about 40-45°, and the water contact angle of the glass plate after coating with the photocatalytic self-cleaning coating is about 160°, indicating that the polydimethylsiloxane modified nano-titanium dioxide photocatalytic self-cleaning glass coating prepared by this method has good hydrophobicity.
[0058] The photocatalytic performance of the polydimethylsiloxane modified nano titanium dioxide photocatalytic self-cleaning glass coating prepared in Example 1 was tested. 5 mg / L methylene blue was selected as the degradation product, and it was first placed in the dark for 30 minutes to complete the adsorption equilibrium, and then degraded under 12W ultraviolet light. The results are as follows: Figure 8 As shown. After about 100 hours of illumination, the degradation rate of methylene blue reached more than 90%, indicating that the polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating prepared by this method has a good photocatalytic degradation effect on organic matter. In addition, Fig. 9 The actual picture of the polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating is shown, and it can be seen that the coating is elastic, tearable and not easy to break.
[0059] Embodiment 2:
[0060] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0061] (2) Add 3.58 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0062] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0063] (4) drying C in an oven at 100°C for 24 h to obtain hydrophobically modified TiO2 particles, i.e., M-TiO2;
[0064] (5) Add 0.5 g of M-TiO2 to 6 mL of n-hexane and disperse by ultrasonic for 30 min;
[0065] (6) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D;
[0066] (7) immersing the glass substrate in a HCl-H2O2 mixture to remove inorganic salts and metal ions on the surface;
[0067] (8) The glass substrate is taken out and ultrasonically treated in deionized water and ethanol solution for 30 min respectively to remove the acid and alkali cleaning solution and residual impurities on the surface, and finally placed in an oven to dry for later use;
[0068] (9) placing the pretreated glass substrate vertically above the coating slurry D, and using a puller to immerse and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0069] (10) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0070] Embodiment 3:
[0071] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0072] (2) Add 6.5 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0073] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0074] (4) drying C in an oven at 100°C for 24 h to obtain hydrophobically modified TiO2 particles, i.e., M-TiO2;
[0075] (5) Add 0.5 g of M-TiO2 to 6 mL of n-hexane and disperse by ultrasonic for 30 min;
[0076] (6) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D;
[0077] (7) Soaking the glass substrate in a mixture of HCl-H2O2 to remove inorganic salts and metal ions on the surface;
[0078] (8) The glass substrate is taken out and ultrasonically treated in deionized water and ethanol solution for 30 min respectively to remove the acid and alkali cleaning solution and residual impurities on the surface, and finally placed in an oven to dry for later use;
[0079] (9) placing the pretreated glass substrate vertically above the coating slurry D, and using a puller to immerse and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0080] (10) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0081] Embodiment 4:
[0082] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0083] (2) Add 12.05 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0084] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0085] (4) drying C in an oven at 100°C for 24 h to obtain hydrophobically modified TiO2 particles, i.e., M-TiO2;
[0086] (5) Add 0.5 g of M-TiO2 to 6 mL of n-hexane and disperse by ultrasonic for 30 min;
[0087] (6) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D;
[0088] (7) immersing the glass substrate in a HCl-H2O2 mixture to remove inorganic salts and metal ions on the surface;
[0089] (8) The glass substrate is taken out and ultrasonically treated in deionized water and ethanol solution for 30 min respectively to remove the acid and alkali cleaning solution and residual impurities on the surface, and finally placed in an oven to dry for later use;
[0090] (9) placing the pretreated glass substrate vertically above the coating slurry D, and using a puller to immerse and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0091] (10) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0092] Embodiment 5:
[0093] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0094] (2) Add 18.15 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0095] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0096] (4) drying C in an oven at 100°C for 24 h to obtain hydrophobically modified TiO2 particles, i.e., M-TiO2;
[0097] (5) Add 0.5 g of M-TiO2 to 6 mL of n-hexane and disperse by ultrasonic for 30 min;
[0098] (6) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D;
[0099] (7) Soaking the glass substrate in a mixture of HCl-H2O2 to remove inorganic salts and metal ions on the surface;
[0100] (8) The glass substrate is taken out and ultrasonically treated in deionized water and ethanol solution for 30 min respectively to remove the acid and alkali cleaning solution and residual impurities on the surface, and finally placed in an oven to dry for later use;
[0101] (9) placing the pretreated glass substrate vertically above the coating slurry D, and using a puller to immerse and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0102] (10) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0103] The difference between Examples 1 to 5 is that the mass ratio of TiO2 to PDMS is changed. This variable mainly has a certain effect on the hydrophobicity and photocatalytic activity of M-TiO2, and then affects the hydrophobicity and photocatalytic activity of the coating. When the mass ratio of the two is too small, the coating has an excellent hydrophobic effect, but the photocatalytic performance is poor. When the mass ratio of the two is too large, the hydrophobic effect of the coating becomes worse, but the photocatalytic performance is better. This can be explained by the changes in the water contact angle and the degradation curve. The results are shown in Figure 7 and 8 As shown, experiments conducted within the mass ratio range mentioned in the present invention can enable the coating to have both good hydrophobicity and photocatalytic activity, among which Example 1 has the best effect.
[0104] Comparative Example 1:
[0105] According to the preparation method proposed in the present invention, a polydimethylsiloxane-modified nano-titanium dioxide photocatalytic self-cleaning glass coating is prepared:
[0106] (1) 0.5 g of TiO2 particles with a particle size of 30 nm were ultrasonically dispersed in 6 ml of THF solution for 30 min at room temperature to form a suspension A;
[0107] (2) Add 9.05 g of PDMS to suspension A at room temperature and stir until THF is completely evaporated to form latex B;
[0108] (3) Then, 10 mL of toluene solution was added to the latex B, stirred evenly, and centrifuged for 10 min. This step was repeated 5 times to remove the residual unreacted PDMS to obtain a wet precipitate C;
[0109] (4) drying the wet precipitate C in an oven at 100°C for 24 h, taking it out and grinding it to obtain hydrophobically modified TiO2 nanoparticles, namely M-TiO2;
[0110] (5) 0.5 g of M-TiO2 was added to 6 mL of n-hexane and ultrasonically dispersed for 30 min, followed by magnetic stirring for 1 h to obtain coating slurry D1;
[0111] (6) Pre-treating a glass substrate according to the method of Example 1, placing the pre-treated glass substrate vertically above the coating slurry D1, and using a puller to dip and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0112] (7) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0113] The coating prepared in Comparative Example 1 is different from that in Example 1 in that PDMS is used only once in the preparation process of Comparative Example 1 to complete the hydrophobic modification of TiO2, and PDMS as a binder is not added for a second time. Obviously, both can achieve the uniformity of inorganic particle dispersion in the coating and the hydrophobicity of the coating surface. In order to illustrate the role of the binder PDMS, the coatings obtained in Example 1 and Comparative Example 1 were subjected to mechanical wear resistance experiments, including tape adhesion tearing and sandpaper friction. The surface of the coating in Comparative Example 1 was severely damaged after being subjected to external friction, and was easily separated from the surface of the glass substrate by the tape, while the coating in Example 1 adhered firmly to the glass substrate, and the surface was still smooth and flat, and good super-hydrophobicity could be maintained.
[0114] Comparative Example 2:
[0115] (1) Add 0.5 g of TiO2 particles with a particle size of 30 nm to 6 mL of n-hexane and ultrasonically disperse for 30 min at room temperature;
[0116] (2) 10.78 g PDMS and 1.078 g curing agent were added, magnetically stirred for 1 h, and finally allowed to stand for 1 h until the bubbles disappeared, to obtain coating slurry D2;
[0117] (3) Pre-treating a glass substrate according to the method of Example 1, placing the pre-treated glass substrate vertically above the coating slurry D2, and using a puller to dip and pull the coating at a rate of 60 mm / s to obtain a wet coating;
[0118] (4) The coated glass substrate is placed at room temperature for 12 hours to solidify, thereby obtaining a dry self-cleaning glass coating.
[0119] The coating prepared in Comparative Example 2 is different from that in Example 1 in that PDMS is used only once in the preparation process of Comparative Example 2, and its function is to enhance the adhesion between inorganic particles and between inorganic particles and the glass substrate, fill cracks and holes on the surface of the material, and repair and reinforce the structure of the material to ensure the durability and stability of the adhesion; the TiO2 used is not hydrophobically modified by PDMS.
[0120] Comparing Example 1 with Comparative Example 2, the dispersibility of the material after PDMS hydrophobic modification in Example 1, namely M-TiO2, in organic solvents such as n-hexane and ethyl acetate is greatly improved, further improving the uniformity of the coating. Fig.10 It can be seen that M-TiO2 is well dispersed in the n-hexane solvent, while the TiO2 particles in Comparative Example 2 that are not hydrophobically modified with PDMS will quickly precipitate at the bottom. Fig.11 The transmission microscope photos of the coatings prepared by the two methods show that, compared with Example 1, the TiO2 in Comparative Example 2 is not evenly dispersed in the solvent, so the TiO2 in the prepared coating is not evenly distributed, which will affect the optical transparency of the coating. Fig.12 The surface water contact angles of the coatings prepared in the two comparative examples and Example 1 are shown. Taking the water contact angle of the uncoated glass surface as a control, it can be seen that compared with Comparative Examples 1 and 2, the coating prepared in Example 1 has more excellent superhydrophobicity.
[0121] In summary, the present invention uses PDMS as a hydrophobic modifier and a binder in two steps to make the coating have better performance.
Claims
1. A polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating, characterized in that, The invention comprises polydimethylsiloxane-modified nano titanium dioxide particles, polydimethylsiloxane, a solvent and a curing agent; the mass ratio of the polydimethylsiloxane-modified nano titanium dioxide particles to the polydimethylsiloxane is 0.5 g:10.78 g; in the polydimethylsiloxane-modified nano titanium dioxide particles, the mass ratio of the nano titanium dioxide particles to the polydimethylsiloxane is (0.05-2) g:(5-20) g; The preparation method of the polydimethylsiloxane modified nano titanium dioxide super-hydrophobic coating comprises: (1) adding polydimethylsiloxane-modified nano-titanium dioxide particles into a solvent and dispersing them by ultrasonication to obtain a modified titanium dioxide solution; (2) adding polydimethylsiloxane and a curing agent to the modified titanium dioxide solution, stirring, and standing until bubbles disappear to obtain the coating; The preparation method of the polydimethylsiloxane-modified nano titanium dioxide particles comprises: 1) Dispersing nano-titanium dioxide particles in a volatile solvent to form a suspension A; in the suspension A, the mass ratio of nano-titanium dioxide particles to polydimethylsiloxane is (0.05-2) g: (5-20) g; 2) Add polydimethylsiloxane to suspension A and stir to evaporate the volatile solvent to form latex B; 3) washing the latex B to obtain a wet precipitate C; 4) Drying the wet precipitate C to obtain polydimethylsiloxane-modified nano-titanium dioxide particles.
2. the preparation method of polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating according to claim 1, is characterized in that, include: (1) adding polydimethylsiloxane-modified nano-titanium dioxide particles into a solvent and dispersing them by ultrasonication to obtain a modified titanium dioxide solution; (2) adding polydimethylsiloxane and a curing agent to the modified titanium dioxide solution, stirring, and standing until bubbles disappear to obtain the coating; The preparation method of the polydimethylsiloxane-modified nano titanium dioxide particles comprises: 1) dispersing nano titanium dioxide particles in a volatile solvent to form a suspension A; In suspension A, the mass ratio of nano-titanium dioxide particles to polydimethylsiloxane is (0.05~2) g: (5~20) g; 2) Add polydimethylsiloxane to suspension A and stir to evaporate the volatile solvent to form latex B; 3) washing the latex B to obtain a wet precipitate C; 4) Drying the wet precipitate C to obtain polydimethylsiloxane-modified nano-titanium dioxide particles.
3. the preparation method of polydimethylsiloxane-modified nano titanium dioxide super-hydrophobic coating according to claim 2, is characterized in that, The solvent is tetrahydrofuran.
4. A polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating, characterized in that: The coating is obtained by coating the coating according to claim 1 on a glass substrate.
5. The method for preparing the polydimethylsiloxane-modified nano titanium dioxide super-hydrophobic coating according to claim 4, characterized in that, The coating according to claim 1 is coated on a glass substrate by a dipping and pulling method, and then cured to obtain the coating.
6. The method for preparing the polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating according to claim 5, characterized in that, Pulling rate: 60~180 mm / s.
7. The method for preparing the polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating according to claim 5, characterized in that: The glass substrate is pre-soaked in a strong acid or alkali solution for cleaning, and then the glass substrate is taken out, cleaned with water and ethanol, and dried.
8. The method for preparing the polydimethylsiloxane modified nano titanium dioxide super hydrophobic coating according to claim 5, characterized in that: The curing is carried out at room temperature for 12 to 24 hours.
Citation Information
Patent Citations
High-durability super-hydrophobic self-cleaning coating material and preparation method thereof
CN101962514A
Self-cleaning coating material with persistent super-hydrophobicity and preparation method thereof
CN109054627A
Photocatalysis super-amphiphobic coating as well as preparation method and application thereof
CN110183880A
Preparation method of reproducible double-self-cleaning super-hydrophobic photocatalytic coating
CN113683953A
Cited By
Heterostructure photocuring conductive coating and preparation method thereof
CN121064707A